2021
DOI: 10.3389/fimmu.2021.768189
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell and Bulk RNA-Sequencing Reveal Differences in Monocyte Susceptibility to Influenza A Virus Infection Between Africans and Europeans

Abstract: There is considerable inter-individual and inter-population variability in response to viruses. The potential of monocytes to elicit type-I interferon responses has attracted attention to their role in viral infections. Here, we use single-cell RNA-sequencing to characterize the role of cellular heterogeneity in human variation of monocyte responses to influenza A virus (IAV) exposure. We show widespread inter-individual variability in the percentage of IAV-infected monocytes. Notably, individuals with high ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…Furthermore, variation in innate immunity 810 – including inborn errors or neutralizing auto-antibodies against type I interferons 11–13 – contribute to the various SARS-CoV-2-related clinical manifestations, and epidemiological and genetic data suggest differences in the outcome of SARS-CoV-2 infection between populations 6,7,14,15 . These observations, together with previous reports on the importance of ancestry-related differences in transcriptional responses to immune challenges 1619 , highlight the need for in-depth investigations of the magnitude of variation in immune responses to SARS-CoV-2 and its drivers across populations worldwide.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, variation in innate immunity 810 – including inborn errors or neutralizing auto-antibodies against type I interferons 11–13 – contribute to the various SARS-CoV-2-related clinical manifestations, and epidemiological and genetic data suggest differences in the outcome of SARS-CoV-2 infection between populations 6,7,14,15 . These observations, together with previous reports on the importance of ancestry-related differences in transcriptional responses to immune challenges 1619 , highlight the need for in-depth investigations of the magnitude of variation in immune responses to SARS-CoV-2 and its drivers across populations worldwide.…”
Section: Introductionmentioning
confidence: 58%
“…7a, b). Individuals of African ancestry also presented higher proportions of CD16 + monocytes 19 and memory lymphocyte subsets, such as memory B cells, effector CD4 + T cells and effector memory CD8 + T cells re-expressing CD45RA (CD8 + EMRA T cells) (Wilcoxon rank-sum p -value < 4.1 × 10 -5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with a previous study using scRNA-seq of IAV-infected cells to link basal expression to susceptibility to infection. 30 In summary, in a single infection, we deconvoluted cells from 48 different individuals and observed highly variable flu burden and transcriptional phenotypes. These methods revealed that baseline IFN levels contribute to resistance against influenza infection.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the amount of viral reads observed in the macrophages post-infection can be used as a surrogate for viral load (Thorburn et al, 2015). Indeed, in a similar experimental system this metric was shown to be stable and reproducible across individuals (O’Neill et al, 2021). Notably, by studying the infected macrophages from these 39 individuals, we observed extensive variation in the levels of viral reads and discovered a set of TEs displaying high inter-individual variability in chromatin accessibility following infection.…”
Section: Introductionmentioning
confidence: 92%